Particle motion over a plane, which rotates about a horizontal axis and makes a certain angle with it - Pylypaka, S.; Klendii, M.; Trokhaniak, V. (Bulletin of the Karaganda University. Mathematics Series, 2019)
Differential equations of relative material particle motion over a plane, which rotates about a horizontal axis, have been set up. Plane location relative to a rotation axis is set by a certain angle, which value can range from zero to ninety degrees. If angle value is equal to zero, a plane passes through a rotation axis; if angle value equals to 90 degrees, it is perpendicular to a rotation axis. The equations have been solved using numerical methods. In case of end positions of an angle, analytical solution has been found.